Spatial and temporal organisation of small mammal communities in the Monte desert, Argentina - Corbalán, Valeria Elizabeth (2004)
The coexistence of desert small mammals can be explained by differences in microhabitat use, morphology, body size, diet and foraging. The aim of this study was to quantify the structure of small mammal assemblages and the seasonal fluctuations in their abundance using mark - recapture techniques in habitats of different structural heterogeneity (mesquite forest, creosotebush community,  and sand dunes) in the temperate Monte desert of Argentina. Habitat heterogeneity was characterised by 10 vegetation variables. The mesquite forest and the creosotebush community showed the highest diversity and habitat heterogeneity. The relative abundance of each species underwent remarkable variations between habitats. The common ?pericote? Graomys griseoflavus and the silky mouse Eligmodontia typus were the dominant species in the mesquite forest and sand dunes, respectively, whereas no dominant species was observed in the creosotebush habitat. Abundance varied throughout the year, reaching maximum density in autumn and spring.